PENYAJIAN LAPORAN KEUANGAN ENTITAS BERORIENTASI NON LABA: STUDI KASUS RUMAH SAKIT PENDIDIKAN - Komalasari, Sanda Patrisia; Edmawati, Sri Dewi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This research aims to provide an overview for hospitals about how to present hospital financial reports using case studies in education hospitals. This research will describe how education hospital presents its financial reports, then this research will also show the quality of the hospital's financial reports and the hospital accountant's understanding of financial reports. The presentation of financial reports for non-profit entities is regulated in ISAK 35. A hospital is a non-profit entity, this means that the hospital uses ISAK 35 in presenting its financial reports. The data in this research was obtained through a survey of financial reports and interview with accountants in charge of presenting financial reports. The education hospital used as the object of this research has fully implemented ISAK 35. The quality of financial reports and the Hospital accountant's understanding of financial reports were found to be very good.